Influence of seasonality on some physiological parameters of three marine fish species, Libya (Journal of Academic Research, 2020)
This study investigated the influence of seasonality on the some biochemical parameters of  liver Pagrus pagrus, Pagrus coerleosticus and Epinephelus guaza. Six specimens of each species of fish  caught from Misurata coast during summer and winter 2017. biochemical analyses of liver crushed were determined using spectrophotometer (Cobas. Integral 400 Plus Roche).  The result showed that, the main biochemical parameters findings were observed in the winter elevated compare with summer of AST, ALP (1257.9±59.3IU/L, 143.96±60.2 IU/L). On the odder hand, ALT and LDH were observed in the summer elevated compare with winter. Furthermore, this study indicated that there are significant (P>0.05) between tow seasonal study of AST, ALP and AST. While P-value of LDH was higher than 0.05 of all seasonal study. The present study that biochemical parameters could be as indicators of physiological status during different seasons of year in those fish species.
Keywords: Liver function; physiology; Liver; Marine fishes